The effect of lenders’ dual holding on loan contract design: Evidence from performance pricing provisions - Lim, Jesslyn; Do, Viet; Vu, Tram (Journal of Banking & Finance, 2022)
Examining a sample of U.S. commercial loans originated between 1996 and 2017, we find that the propensity to employ performance pricing provisions (PPPs) in private loan contracts increases by about 10% when lenders are dual holders, that is, when they simultaneously hold equity in the borrowing firm. This finding supports the monitoring efficiency channel and is robust after accounting for the endogeneity bias from lenders’ dual holding. We also observe a substitution effect between PPP usage and covenant tightness, and the strength of this effect in dual-holder loans varies between spread-increasing and spread-decreasing PPPs. Borrowers of dual-holder loans are more likely to improve their accounting performance within one year of loan origination. These findings are consistent with dual holders’ incentive alignment role, which helps reduce monitoring costs, improve lenders’ monitoring effectiveness, and promote managerial flexibility.